Ratio of linear function of parameters and testing hypothesis of the combination two split plot designs - Usman, Mustofa; Elfaki, Faiz Ahmed Mohamed; Daoud, Jamal Ibrahim (IDOSI Publications, 2013)
The aim of this paper is going to analyze comparison of ratio of parameters and testing various hypotheses of the combination two split plot designs. The combination of two fixed effect split plot designs have constrains on its parameter and the model is non full rank model. First we transform the model into two models, one model related to whole plots and the other model related to split plot. By Model reduction Methods, we transform each model into unconstraint model with full column rank. Based on these unconstraint models estimation, ratio of linear function of parameters by using Fieller’s Theorem and testing various hypotheses will be developed.